Kepemilikan Umum dalam Pandangan Islam - Maharati, Cindy (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
The significant difference between the conventional economic system and the Islamic Economic System can be seen from the ownership rules. If in the conventional economic system that we adhere to factually today, individual ownership has no limits and the absolute requirement for the system to run is the free market mechanism. Whereas in the Islamic Economic System, ownership rules are divided and regulated on the basis of sharia, and the operation of the system is absolute on the basis of sharia laws. Islamic economics regulates human economic procedures since humans want to own property. Humans must understand the division of ownership of God's treasures on this earth. Which part of the property is legally allowed to be owned by individuals, which part is included in public ownership, and which part belongs to the state.